2021
DOI: 10.1176/appi.ps.202000080
|View full text |Cite
|
Sign up to set email alerts
|

Help and Hindrances to Completion of Psychiatric Advance Directives

Abstract: Psychiatric advance directives (PADs) allow service users to participate in their own mental health care in the event that they have a future mental health crisis and are deemed incompetent to make decisions, but few patients complete these documents. This Open Forum reports on factors that have helped or hindered completion of PADs in New Zealand. Perceived barriers to completion include resource limitations, procedural issues, access and storage problems, and mistrust between clinicians and service users reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…These findings build on a developing body of international literature which has confirmed an aspiration/implementation gap for mental health ADM and outlined barriers to implementation. Hypothesised implementation strategies to address these barriers have included: facilitation of ADM documents ( Ruchlewska et al, 2014 ; Swanson et al, 2006b ), appointing clinical champions ( Zelle et al , 2015 ), stakeholder outreach meetings ( Lenagh-Glue et al , 2021 ), training and IT support ( Stephenson et al, 2020b ; Zelle et al , 2015 ). This study adds to this literature in that it: offers a deeper exploration of the reasons why support is so crucial for service users in managing trauma and power differentials, addresses key issues in producing materials and processes for ADM, generates and evaluates multiple co-produced implementation strategies, clarifies stakeholders and organises these co-produced implementation strategies within a recognised framework ready for future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings build on a developing body of international literature which has confirmed an aspiration/implementation gap for mental health ADM and outlined barriers to implementation. Hypothesised implementation strategies to address these barriers have included: facilitation of ADM documents ( Ruchlewska et al, 2014 ; Swanson et al, 2006b ), appointing clinical champions ( Zelle et al , 2015 ), stakeholder outreach meetings ( Lenagh-Glue et al , 2021 ), training and IT support ( Stephenson et al, 2020b ; Zelle et al , 2015 ). This study adds to this literature in that it: offers a deeper exploration of the reasons why support is so crucial for service users in managing trauma and power differentials, addresses key issues in producing materials and processes for ADM, generates and evaluates multiple co-produced implementation strategies, clarifies stakeholders and organises these co-produced implementation strategies within a recognised framework ready for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…A recent randomised controlled trial in France also concluded that ADM documents completed by service users with SMI supported by peer workers resulted in significantly fewer compulsory admissions ( Tinland et al , 2022 ). Interestingly, the New Zealand experience suggested that more service users were able to complete their document with a clinician, the key factor being trust rather than nature of the facilitator’s previous experience ( Lenagh-Glue et al , 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…• Use the advance care agreement to guide discussions, with the patient, about their preferences in relation to the use of (e.g.) expressive touch, and refer to this agreement regularly when supporting the patient (Lenagh-Glue et al, 2018).…”
Section: Overcoming the Challengesmentioning
confidence: 99%
“…ADs support people to exercise their capacity to make decisions, in advance, when they might have difficulty formulating or articulating choices later. In our research, we have sought to determine how ADs can be used most effectively in mental health care in New Zealand (Lenagh-Glue et al, 2018, 2021).…”
Section: Introduction: Advance Directives For Mental Health Carementioning
confidence: 99%